The Law and Ethics of Switching from Biologic to Biosimilar in Canada. Issue 5 (3rd January 2020) - Murdoch, Blake; Caulfield, Timothy
Abstract: Governments and financial institutions in several jurisdictions are planning or implementing nonmedical/'forced' switches by cutting drug coverage for reference biologics and funding only less expensive biosimilars. Switches raise numerous ethical and legal challenges, as the drugs are framed as not being identical and, despite strong evidence for noninferiority of some biosimilars, there is controversy over whether switching can sometimes lead to adverse events. Canadian law generally requires physicians to give precedence to their patients' best interests over social interests such as cost containment. The primacy of patients' interests is also clearly reflected in professional policies and codes of ethics. Moreover, physicians are obligated to disclose everything a reasonable person in the patient's position would want to know when obtaining informed consent for treatment, including addressing not only scientific information but also relevant social controversy about nonmedical switches. Under Canadian law, physicians may be obligated to tell patients about the ability to access unfunded biologics, even if patients lack the resources to obtain them. In sum, while there is no inherent right to funding for reference biologics in Canada, physicians in some circumstances may have a legal obligation as fiduciaries to advocate on behalf of patients to remain on a reference biologic. At a minimum, the controversy surrounding switching will necessitate, as part of the consent process, a robust and thorough disclosure of relevant risks, benefits and reasonable alternatives.